Job mobility as a new explanation for the immigrant-native wage gap: A longitudinal analysis for the German labor market - Hanna Brenzel; Malte Reichelt (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
Theoretically, wage gaps between migrants and natives can be explained by human capital theory through either depreciation in human capital with migration or differences in endowments. However, even after considering human capital measures, an unexplained difference remains. We assume that differences in the employment trajectories of migrants and natives contribute to wages that diverge after labor market entrance. Utilizing a rich longitudinal data set (ALWA-ADIAB), we analyze the job mobility of migrants and natives in Germany and distinguish among voluntary, involuntary, internal and other job changes. Indeed, we find evidence for differences in transition patterns and - using several fixed-effects regressions - are able to explain a substantial part of the gap between migrants' and natives' hourly wages by differences in job change behavior. – – Theoretisch lassen sich Lohnunterschiede zwischen Migranten und Einheimischen mithilfe der Humankapitaltheorie erklären. Diese unterstellt Ausstattungsunterschiede oder eine Abwertung von Humankapital bei Migration. Trotzdem bleibt auch nach Berücksichtigung von Humankapital-Variablen meist ein unerklärter Lohnunterschied zwischen Migranten und Einheimischen. Wir benutzen einen umfangreichen Längsschnittdatensatz (ALWA-ADIAB) und analysieren die Arbeitsplatzmobilität von Migranten und Einheimischen in Deutschland, wobei wir zwischen freiwilligen, unfreiwilligen, internen und anderen Wechseln unterscheiden. Wir finden unterschiedliche Übergangsmuster und können - mithilfe von fixed-effects Regressionen - einen substantiellen Teil der Lohnlücke mit Unterschieden im Jobwechsel-Verhalten erklären.
Keywords: J61; J31; J62; J15; 330; migration; wage inequality; migrant wage gap; fixed-effects regression; ALWA-ADIAB